Arabic Grammar Traditions in Gibe and Harär: Regional Continuity vs Specificity of Scholarship - Fani, Sara (Aethiopica, 2017)
The present study is based on the analysis of manuscript collections of two regions of Ethiopia in part collected during two field missions and in part already known. Gibe and Harär areas were chosen both for the interesting history of their Islamisation and for their location directed towards West and North Africa from the one side, and East Africa and the Arabian peninsula from the other. Among the different fields of Islamic education, Arabic grammar has been identified as a subject not specific to certain collections or areas, being Arabic learning at the base of every Islamic curriculum studiorum. The traditional core curriculum for Arabic learning has been determined according to the presence of traditional grammar works together with their comments, abridgements, glosses etc. in order to highlight possible specificities or common traditions between the two areas and between these and the surrounding regions through implicit intellectual networks along the historical trade routes.